(untitled) (Research, Society and Development, 2022)
The chronicity of musculoskeletal algia in the clinical picture in fibromyalgia, associated with stages of sharpness, for various reasons of time, emotional, physical, labor and social, instigates the need for appropriate and effective therapies for the maintenance of functionality and quality of life, in view of the absence of cure. This research aimed to measure the effects of physical therapy in pilates directed to the chronic stage of fibromyalgia, given the complexity of impairments related to signs and symptoms. 15 pilates sessions were performed 3 times a week, with protocol parameters according to the clinical picture of the disease. The Fibromyalgia Impact Questionnaire (QIFR-Br) quantified pain intensity, functionality and quality of life before and after the intervention. The statistical analysis showed statistically significant results (p<0.05) for all variables, i.e., the proposed protocol is effective for restoring functionality, due to analgesia, achieved with kinesiotherapy, providing better prognosis and stabilization of the clinical picture.